A case for curriculum renewal: Deficiencies in the training of prospective auditors in a technology era - Rudman, R.; Sexton, N.D. (South African Journal of Higher Education, 2020)
The information revolution, where the evolution of technology has a pervasive impact on all aspects of life and business, is upon us. The private sector has embraced new technologies, presenting opportunities while also giving rise to new risks. Although slow to start, organisations (or audit clients – auditees) have started implementing specialist information technology (IT) governance frameworks to mitigate the risks attributable to IT. Just as organisations have changed, it is expected that external auditors (auditors), and their education and training, would also have adapted their audit approaches to account for the impact of evolving IT on auditees. This has not necessarily been the case. The standards do not provide the necessary detail guidance on IT required by auditors. The university curriculum as well as supplementary text have neither kept up to date with the rapid changes in technology or the changes in governance frameworks. The objective of this research was to perform a curriculum audit of the sufficiency of the auditing text (i.e. International Standards on Auditing (ISAs) and supporting guidances and textbooks as required by the competency framework) used in the audit specialisation of training prospective CAs (i.e. the curriculum relating to IT as part of the audit process) in ensuring graduates (i.e. future auditors) are relevant in an ever-evolving IT-driven environment The study found that although several areas of the audit curriculum are appropriate, there is in fact a gap within the current curriculum relating to IT internal controls and risks that exist at a technology level. The study calls for curriculum renewal within the audit specialisation, giving specific consideration to technology or operational-level controls within the framework of general and application IT internal controls taught.